LOCAL ANESTHETICS INDUCED ALLERGIC REACTIONS AND CONFOUNDING FACTORS - Andrei Gheorghe Vicovan; Irina Teodora Cernescu; Liliana Vereș; Irina Gradinaru; Cristina Mihaela Ghiciuc (Romanian Society of Oral Rehabilitation, 2019)
The local anesthetics (LAs) immediate-type allergy is considered extremely rare by allergists. However, many health care practitioners and patients overestimate the risk of LA allergy and its potential of cross-reactivity. The aim of this paper was to identify the confounding factors for the diagnosis of an allergic reaction induced by a local anesthetics for a patient who needs local anesthesia during dental procedures. Material and methods. Studies selected from PubMED and from Web of Science (all databases) regarding the confounding factors for diagnostic of local anesthetics-induced allergic reactions during dental procedures were included. We recorded the confounding factors for diagnostic and management of allergic reactions during dental procedures. Results. From the 34 papers retrieved, there were selected only the clinical studies that mentioned the confounding factors for diagnostic of local anesthetics-induced allergic reactions during dental procedures (8 papers). The number of real LA-induced immediate-type allergy is very low (one retrospective study confirmed only 4 LAs-allergy cases: 1 to mepivacaine, 1 to prilocaine, 2 to articaine) within the past 20 years on 402 patients referred to allergist for diagnostic. The allergic reactions are due to vasopressors and bisulfites that are included as antioxidants. Conclusion. Most commonly the reactions have an underlying nonallergic mechanism such as vasovagal reactions, or are conditioned by simultaneous contact with other potential allergens such as chlorhexidine, antibiotics or latex.